Exendin-4 regulates the MAPK and WNT signaling pathways to alleviate the osteogenic inhibition of periodontal ligament stem cells in a high glucose environment - Wang Min; Liu Min; Zheng Jiawen; Xiong Li; Wang Ping (Open Medicine, 2023)
Diabetes mellitus (DM) increases the destruction of periodontal tissue and impairs osteogenesis differentiation. Exendin-4 (Ex-4), a glucagon-like peptide-1 (GLP-1) analogue, can be used for treating DM and promotes bone regeneration. The aim of this study was to explore the effect and mechanism of Ex-4 on improving the osteogenesis of periodontal ligament stem cells (PDLSCs) in a high glucose environment. Alkaline phosphatase staining and alizarin red staining were used to detect the osteogenic differentiation of PDLSCs. The results showed that 10 nM Ex-4 could reduce the osteogenesis inhibition of PDLSCs induced by high glucose. RT-PCR and western blot results showed that Ex-4 increased the osteogenesis-related gene expression of ALP, Runx2, and Osx, and upregulated the phosphorylation of P38, JNK, and ERK1/2; the peak effect was observed in the range 0.5–1.0 h. Mitogen-activated protein kinase (MAPK) inhibitors PD98059, SB203580, and SP600125 blocked the effects of Ex-4 on MAPK activation and decreased the expression of ALP, Runx2, and Osx in PDLSCs. Moreover, after Ex-4 treatment, the total β-catenin, p-GSK3β, LEF, and Runx2 protein levels increased under normal or high glucose environments. In conclusion, our results indicated that Ex-4 regulates the MAPK and WNT signaling pathways to alleviate the osteogenic inhibition of PDLSCs in a high glucose environment.